2018
DOI: 10.15560/14.5.893
|View full text |Cite
|
Sign up to set email alerts
|

Birds of Estação Ecológica da Serra das Araras, state of Mato Grosso, Brazil: additions and review

Abstract: We present an inventory, followed by a consolidated list, for the avifauna of Estação Ecológica da Serra das Araras (EESA), state of Mato Grosso, Brazil. In our expeditions, we identified 287 species, 82% of them documented. Of these, 28 species are new records for EESA. Six are threatened, such as Lophornis gouldii (Lesson, 1832). Other noteworthy records include the first documentation of Oxyruncus cristatus Swainson, 1821, for Mato Grosso. The consolidated list includes 458 species, of which 255 were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
1
12
0
2
Order By: Relevance
“…PEBI species richness (172 bird species) is similar to other surveys carried out in Cerrado areas in Brazil, which generally present between 151 -287 species (see Rodrigues et al 2005, Marçal Júnior et al 2009, Rodrigues et al 2011, Vitorino et al 2018, corresponding to approximately 20% of the bird species of Cerrado (Silva & Santos 2005). Habitat diversity in the study area is distributed in a mosaic landscape (Marques & Nakajima 2015), that offer a variety of habitat types for animal and plant species inserted in an ecotone between the two major hotspots in Brazil: the Cerrado and the Atlantic Forest (Myers et al 2000, Pereira et al 2015.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…PEBI species richness (172 bird species) is similar to other surveys carried out in Cerrado areas in Brazil, which generally present between 151 -287 species (see Rodrigues et al 2005, Marçal Júnior et al 2009, Rodrigues et al 2011, Vitorino et al 2018, corresponding to approximately 20% of the bird species of Cerrado (Silva & Santos 2005). Habitat diversity in the study area is distributed in a mosaic landscape (Marques & Nakajima 2015), that offer a variety of habitat types for animal and plant species inserted in an ecotone between the two major hotspots in Brazil: the Cerrado and the Atlantic Forest (Myers et al 2000, Pereira et al 2015.…”
supporting
confidence: 83%
“…Transitional areas, as the Central Espinhaço Range, tend to harbor higher species richness and abundance, because they support overlapping communities that would normally be restricted to isolated ecosystems (Kark et al 2007, Vitorino et al 2018, Sementili-Cardoso et al 2019). However, these transitional areas tend to receive less attention in biodiversity research than distinct ecosystems (Sementili-Cardoso et al 2019).…”
mentioning
confidence: 99%
“…Some of the studies found in our search were carried out on the Pantanal Plateau (i.e. Vitorino et al 2018), which is also threatened by these activities. Studies aimed at the conservation of the Pantanal should also direct their efforts at protecting the plateau and supporting the Paraguay watershed.…”
Section: Discussionmentioning
confidence: 99%
“…For the general list of birds, each species was reviewed and separated into three lists according to the methodology adopted by Piacentini et al (2015) and other check list studies (Nunes et al 2017;Vitorino et al 2018):…”
Section: Introductionmentioning
confidence: 99%
“…The general list is, thus, composed of species from the primary and secondary lists. The documentation type of ornithological records was based on Carlos et al (2010), even as applied to another protected area in Brazil (Vitorino et al 2018): "A-level documentation" for species with specimens deposited in scientific collections; "B-level documentation" for species documented with photographs or audio recordings; and "Indication of Occurrence" for species recorded in the field, but not documented.…”
Section: Introductionmentioning
confidence: 99%